Panophthalmitis After Aurolab Aqueous Drainage Implant (AADI) in Refractory Glaucoma with Vogt-Koyanagi-Harada Syndrome (VKH): A Case Report - Iftekher Iqbal, Md; Jahangir Kabir, Syed; Kumer De Sarker, Bipul (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
This case of Vogt-Koyanagi-Harada (VKH) disease underwent Aurolab Aqueous Drainage Implant (AADI) for refractory glaucoma. Later, developed postoperative (2 months) panophthalmitis characterized by sudden visual loss, moderate pain, redness, and purulent discharge. Systemic, topical, and intravitreal antibiotic therapy was started immediately, and evisceration was performed.